DEVELOPING STRATEGIES OF AGROTOURISM X - Ajeng Uswatun Hasanah; Fitria Dina Riana; Deny Meitasari (Socio-Economics/Agribusiness Department, 2023)
Agrotourism is a series of tourism activities related to optimizing the potential of agriculture as a tourist attraction. The development of agrotourism can be done with resources, increasing the income of farmers or local communities, and choice preposition. Currently, agrotourism is widely spread in various regions, one of which is Agrotourism X. As a new business unit, Agrotourism X experienced various obstacles including a less strategic business location, facilities, infrastructure that agreement not maximized, limited agrotourism area, capital sourced from personal funds, and choice activities carried out were still not optimal. This study uses descriptive statistical analysis. The criteria for respondents in this study were tourists who had visited Agrotourism X and consumed the product at least once. The data collection technique was carried out by interviewing as well as using a questionnaire with an online questionnaire instrument via Google Form. Processing of research data is carried out using SWOT analysis and QSPM (Quantitative Strategy Planning Matrix). The priority that can be applied based on the QSPM analysis to be implemented is product development. This strategy has the highest TAS value among other alternative strategies, which is 7.5 based on developing product or second strategy.